Tanggung Jawab Pelaku UMKM Sebagai Merchant Dalam E-commerce - Tuhumena, Since; Narwadan, Theresia Nolda Agnes; Fataruba, Sabri (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The dynamics of globalization and technological advances have changed the business world significantly, especially with rapid developments in the field of electronic commerce (e-commerce). Significant growth in this field is expected to make a positive contribution to the development of Micro, Small and Medium Enterprises (MSMEs) by expanding market access.Purposes of the Research: To find out and analyze the responsibilities of MSME actors as merchants in e-commerce.Methods of the Research: The legal research method used in studying this problem is normative juridical, which is based on primary, secondary and tertiary legal materials, and uses a statutory approach and a conceptual approach.Results of the Research: The results of this research show that quite a few business actors do not fulfill their obligations, namely being responsible for fulfilling consumer rights. The form of consumer rights that is violated by business actors in a food product for consumption by consumers is stated in Article 4 point (3) regarding the provision of correct and clear information about a product, goods and/or services. Therefore, business actors are obliged to follow food production standards and maintain product quality in order to meet consumer needs and satisfaction. To protect consumers from business actors whose rights are not fulfilled, the Consumer Protection Law provides protection to consumers in two forms, namely preventatively and repressively. By using strict liability, the application of absolute responsibility solves problems faced by consumers without the need to prove fault, so that consumer rights based on this responsibility can provide legal protection